2001
DOI: 10.4049/jimmunol.166.12.7419
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Immune Response and Protective Immunity to a Japanese Encephalitis Virus DNA Vaccine by Coadministration of an IL-12-Expressing Plasmid

Abstract: IL-12 plays a central role in both innate and acquired immunity and has been demonstrated to potentiate the protective immunity in several experimental vaccines. However, in this study, we show that IL-12 can be detrimental to the immune responses elicited by a plasmid DNA vaccine. Coadministration of the IL-12-expressing plasmid (pIL-12) significantly suppressed the protective immunity elicited by a plasmid DNA vaccine (pE) encoding the envelope protein of Japanese encephalitis virus. This suppressive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
6
20
0
Order By: Relevance
“…The p18-specific CD8 ϩ response in mice receiving plasmid IL-12 on day 0 was diminished compared to that of mice receiving the gp120 DNA alone. These data are consistent with reports demonstrating the suppressive nature of plasmid IL-12 when given at high concentrations concurrently with antigen (5,8,15). While further dose titration studies demonstrated that 20 g of PMV-IL-12 administered concurrently with gp120 DNA could increase the early expansion phase of the p18-specific CTL response, this augmentation was transient, with CTL declining to levels comparable to those observed in mice immunized with gp120 alone as the response reached its plateau phase (data not shown).…”
Section: Durable Augmentation Of Hiv-1 Gp120 Dna Vaccine-elicited Cd8supporting
confidence: 92%
“…The p18-specific CD8 ϩ response in mice receiving plasmid IL-12 on day 0 was diminished compared to that of mice receiving the gp120 DNA alone. These data are consistent with reports demonstrating the suppressive nature of plasmid IL-12 when given at high concentrations concurrently with antigen (5,8,15). While further dose titration studies demonstrated that 20 g of PMV-IL-12 administered concurrently with gp120 DNA could increase the early expansion phase of the p18-specific CTL response, this augmentation was transient, with CTL declining to levels comparable to those observed in mice immunized with gp120 alone as the response reached its plateau phase (data not shown).…”
Section: Durable Augmentation Of Hiv-1 Gp120 Dna Vaccine-elicited Cd8supporting
confidence: 92%
“…L929 cells, infected with JEV 16-18 h before the assay, were used as target cells, as described previously [27]. Then, the target cells were distributed into wells of a U-bottom 96-well plate (5 × 10 3 cells/well) in triplicate, followed by addition of the effector cells at various effector: target (E:T) ratios (50:1, 100:1 and 200:1).…”
Section: Ctl Assaymentioning
confidence: 99%
“…This decrease in the Th1 bias may also be due to Th1 immunosuppressive effects produced by IL-12. This phenomenon has been described by Chen and co-workers who demonstrated that the administration of an IL-12 expression plasmid as an adjuvant adversely affected T-cell responses to the vaccine under certain conditions (Chen et al, 2001). More recently, studies have shown that IL-12 is required for the expansion of Th1 cells rather than for the initiation of a Th1-type immune response (Trinchieri et al, 2003).…”
Section: Discussionmentioning
confidence: 76%